Liver Injury Following Isoniazid Preventive Therapy in HIV Patients Attending Halibet National Referral Hospital, Eritrea: A Prospective Cohort Study - Mulugeta Russom; Daniel Y. B. Jeannetot; Araia Berhane; Henok G. Woldu; Bruno H. Stricker; Katia M. C. Verhamme (Adis, Springer Healthcare, 2023)
Abstract Introduction A 6-month course of isoniazid, 300 mg daily, was programmatically introduced in Eritrea in 2014 as tuberculosis preventive therapy in people living with human immunodeficiency virus (PLHIV). The rollout of isoniazid preventive therapy (IPT) in PLHIV was successful in the first 2-3 years. After 2016, rumours based on rare but real incidents of liver injuries following use of IPT spread widely across the country and created concerns amongst healthcare professionals and consumers, that ultimately caused dramatic decline in the rollout of the intervention. Decision makers have been demanding better evidence as previously conducted local studies had inherent methodological limitations. This real-world observational study was conducted to evaluate the risk of liver injury associated with IPT among PLHIV attending Halibet national referral hospital, Asmara, Eritrea. Methods A prospective cohort study, that consecutively enrolled PLHIV attending Halibet hospital, was conducted between 1 March and 30 October 2021. Those exposed to anti-retroviral therapy (ART) plus IPT were considered as exposed and those taking only ART were considered as unexposed. Both groups were prospectively followed up for 4-5 months with monthly liver function tests (LFTs). A Cox proportional hazard model was used to explore whether there was increased risk of drug-induced liver injury (DILI) associated with IPT. Probability of survival without DILI was also estimated using Kaplan-Meier curves. Results A total of 552 patients, 284 exposed and 268 unexposed, completed the study, with a mean follow-up time of 3.97 (SD 0.675) months for the exposed and 4.06 (SD 0.675) months for the unexposed. Twelve patients developed drug-induced liver injury (DILI), with a median time-to-onset of 35 days (interquartile range: 26.8, 60 days). All cases were from the exposed group and all except two cases were asymptomatic. The incidence rate of DILI in the exposed group was 10.6 cases per 1000 person-months and zero for the unexposed group (p = 0.002). Conclusion DILI in PLHIV taking IPT was common; therefore, liver function should be closely monitored to safely administer the product. Despite high levels of deranged liver enzymes, the majority had no symptoms of DILI, emphasising the importance of close laboratory monitoring, especially during the first 3 months of treatment.